STUDI TENTANG MONUMEN SIMPANG TIGO DI KECAMATAN LUBUK BASUNG - MISNA DESWITA, Drs. Erfahmi,M.Sn, Dra. Lisa Widiarti, M.Sn (Universitas Negeri Padang, 2015)
The purpose of the research: (1) to know the structure of SimpangTigo Monumen, (2) to know the fungtion of Simpang Tigo Monumen, (3)to know the meaning of Simpang Tigo Monumen. This research isconducted by using kualitative method with descriptive research. The dataof this research are oral, documentation as primer data from informant and the secunder data is a written from library.The data of this research is collected from observation, interview,documentation and bibliography. The result of this research is the structureof monument: the middle and the under. The fungtion of monument issymbol of Agam regency. The meaning of monument come from pilosofiMinangkabau tradition,“Tungku nan Tigo Sajarangan, Tali nan Tigo Sapilin”.Kata kunci : Monument, strukture, fungtion dan meaning